Skarn radiogeochemical features; Geochemistry International; Vol. 22, iss. 6 - Rikhvanov L. P. Leonid Petrovich (1985, 1985)
Data are given on the behaviour of U and Th during skarn formation. The concentrations and forms of these elements in main skarn minerals are considered. The skarns in the region are characterized by an influx of U and reduction in the Th/U ratios. The elevated U concentrations were produced by infiltrating hydrothermal solutions.